Investigation on microstructures, compressive properties and energy absorption capacity of carbon nanotubes/aluminum composite foam-filled tubes. (15th February 2022) - Yang, Xudong; Feng, Xiaolin; An, Tao; Yang, Kunming; Sha, Junwei; Zhao, Naiqin; Zong, Rongrong
Abstract: This study presents the results of quasi-static compressive tests of aluminum (Al) foam-filled tubes (A-FFTs) and Carbon Nanotubes (CNTs)/Al composite foam-filled tubes (C-FFTs) prepared by in-situ filling space-holder method. The effects of processing parameters and interface interaction between foam fillers and tubes on mechanical properties and deformation behaviors of the C-FFTs are analyzed, through both the macro- and micro-scopic characterizations. The results show that both cold pressing and sintering can improve the interface connection between foam fillers and tubes. Besides, the addition of CNTs not only increases the strength of foam fillers, but also changes the deformation mode of foam fillers from layer-by-layer shear failure to overall shear failure, which in turn influences the mechanical properties of foam-filled tubes (FFTs). Meanwhile, the interface between foam fillers and tubes (macro interface) of the A-FFTs shows a metallurgical bonding because of the atom diffusion during cold pressing and sintering processes, and as a result, the energy absorption capability of the A-FFTs and 2.5 wt% C-FFTs are increased by 51.3% and 45.8%, respectively. Based on the current findings, a distinctive deformation behavior associated with the interaction effect is proposed.